Weighted Inequality - Ghimire, Santosh (Journal of the Institute of Engineering, 2014)
In this paper, we define Ap weights, briefly discuss the theory of weighted inequalities and its application and importance in various fields. We then prove that for an Ap weight function w and for some , the function, min(w, k) is an Ap weight function. Finally we establish the weighted inequality for min(w, k). DOI: http://dx.doi.org/10.3126/jie.v10i1.10887 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014 pp. 121–124